AS METAMORFOSES DO MUNDO DO TRABALHO E SEUS REFLEXOS NA EDUCAÇÃO (Razão e Fé, 2022)
This article reflects on how the metamorphoses of the world of work, led by neoliberalism in recent centuries, have directly influenced education as a way of maintaining a dominant ideology. In other words, the one that reproduces the capital-labor relationship by forming a subaltern and fragmented workforce, making it difficult to build the foundations for another societal project, more just and solidary.